Political Economy of Mechanisms - Acemoglu, Daron; Golosov, Michael; Tsyvinski, Aleh (Econometrica, 2008)
We study the provision of dynamic incentives to self-interested politicians who control the allocation of resources in the context of the standard neoclassical growth model. Citizens discipline politicians using elections. We show that the need to provide incentives to the politician in power creates political economy distortions in the structure of production, which resemble aggregate tax distortions. We provide conditions under which the political economy distortions persist or disappear in the long run. If the politicians are as patient as the citizens, the best subgame perfect equilibrium leads to an asymptotic allocation where the aggregate distortions arising from political economy disappear. In contrast, when politicians are less patient than the citizens, political economy distortions remain asymptotically and lead to positive aggregate labor and capital taxes.